Clinical and Microbiological Evaluation of a Chlorhexidine-Modified Glass Ionomer Cement (GIC-CHX) Restoration Placed Using the Atraumatic Restorative Treatment (ART) Technique - Ratnayake, J.; Veerasamy, A.; Ahmed, H.; Coburn, D.; Loch, C.; Gray, A.R.; Lyons, K.M.; Heng, N.C.K.; Cannon, R.D.; Leung, M.; Brunton, Paul (MDPI, 2022)
The aims of this study were to investigate the clinical effectiveness and patient acceptability of a modified glass ionomer cement placed using the atraumatic restorative treatment (ART) technique to treat root caries, and to carry out microbiological analysis of the restored sites. Two clinically visible root surface carious lesions per participant were restored using ART. One was restored with commercial glass ionomer cement (GIC) (ChemFil® Superior, DENTSPLY, Konstonz, Germany) which acted as the control. The other carious root lesion was restored with the same GIC modified with 5% chlorhexidine digluconate (GIC-CHX; test). Patient acceptability and restoration survival rate were evaluated at baseline and after 6 months. Plaque and saliva samples around the test and control restorations were collected, and microbiological analysis for selected bacterial and fungal viability were completed at baseline, and after 1, 3, and 6 months. In total, 52 restorations were placed using GIC and GIC-CHX in 26 participants; 1 patient was lost to follow-up. After reviewing the restorations during their baseline appointments, participants indicated that they were satisfied with the appearance of the restorations (n = 25, 96%) and did not feel anxious during the procedure (n = 24, 92%). Forty-eight percent (n = 12) of the GIC-CHX restorations were continuous with the existing anatomic form as opposed to six for the GIC restorations (24%), a difference which was statistically significant (p = 0.036). There was no statistically significant reduction in the mean count of the tested microorganisms in plaque samples for either type of restorations after 1, 3, or 6 months. Restoration of carious root surfaces with GIC-CHX resulted in higher survival rates than the control GIC. ART using GIC-CHX may therefore be a viable approach for use in outreach dental services to restore root surface carious lesions where dental services are not readily available, and for older people and special needs groups.